Assessing the uptake of the Liverpool Care Pathway for dying patients: a systematic review. Issue 4 (25th May 2013) - Stocker, Rachel; Close, Helen
Abstract : Improving the care of the dying is regarded as a national priority and current guidelines stipulate the need to provide holistic palliative care. Despite this, many dying patients and carers report low levels of comfort and satisfaction with care. Reasons include poor coordination of care, variability in communication and crisis-driven interventions. Integrated care pathways aim to support care coordination and open communication with patients and carers. One example is the Liverpool Care Pathway (LCP). Using the LCP entails assessment of eligibility criteria which requires skills, knowledge and clinical judgement about its timing. This can be problematic, and little is known about actual uptake, characteristics of assessed patients and reasons for inclusion/exclusion. A comprehensive systematic review was conducted for papers published between January 1990 and July 2012 providing information on LCP uptake. 17 papers met inclusion criteria. A total of 18 052 patients were placed on the LCP, in a variety of inpatient and primary care settings, and cancer and non-cancer diagnoses. 47.4% of dying patients identified were placed on the LCP. Although the LCP is widely recommended, it is only used for around half of dying patients. Reasons may include lack of knowledge, high staff turnover and concerns about applicability particularly for unpredictable dying trajectories. The proportion of patients who meet the eligibility criteria and the reasons surrounding low uptake remain unclear. Research is urgently required to further quantify the variable use of the LCP, and to investigate whether alternative approaches should be developed for non-cancer groups.